Kesehatan Mental Pengasuh Informal pada Masa Pandemi Covid-19 (Sebuah Tinjauan Sistematis) - Pratiwi, Ni Putu Padmadita Nanda; Hartini, Nurul (Universitas Islam Indonesia, 2022)
Informal caregivers are not only at risk to physical health problems but also mental health problems as they take care of patients, especially during COVID-19 pandemic. This is caused by changes in daily activities routine and structure as well as the increased burden in taking care the patients as the consequence of reduced access to formal health services. However the role of informal caregiver is often underappreciated. The study aims to describe the mental health condition of informal caregivers in taking care the patients during the COVID-19 pandemic. The reviews were conducted on two sites which prove the online journals, they are Google Scholar and ScienceDirect and it found nine journal research. The nine journals were evaluated using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). The findings show that mental health condition of informal caregivers can be observed from emotional, cognitive, and behavioral variables, with the aspects such as anxiety, fear, distress, depression, quality of life, telehealth, suicidal ideation, health protocol, and changes in lifestyle. Whether caregiving duties during COVID-19 pandemic solely cause mental health problems for informal caregivers remains unclear. Findings from this research are expected to facilitate upcoming research, especially in psychological variables related to informal caregivers who take care patients in the time of COVID-19 pandemic.